Consumer confusion about wholegrain content and healthfulness in product labels: a discrete choice experiment and comprehension assessment. Issue 18 (10th December 2020) - Wilde, Parke; Pomeranz, Jennifer L; Lizewski, Lauren J; Zhang, Fang Fang
Abstract: Objective: Using a legal standard for scrutinising the regulation of food label claims, this study assessed whether consumers are misled about wholegrain (WG) content and product healthfulness based on common product labels. Design: First, a discrete choice experiment used pairs of hypothetical products with different amounts of WG, sugar and salt to measure effects on assessment of healthfulness; and second, a WG content comprehension assessment used actual product labels to assess respondent understanding. Setting: Online national panel survey. Participants: For a representative sample of US adults ( n 1030), survey responses were collected in 2018 and analysed in 2019. Results: First, 29–47 % of respondents incorrectly identified the healthier product from paired options, and respondents who self-identified as having difficulty in understanding labels were more likely to err. Second, for actual products composed primarily of refined grains, 43–51 % of respondents overstated the WG content, whereas for one product composed primarily of WG, 17 % of respondents understated the WG content. Conclusions: The frequency of consumer misunderstanding of grain product labels was high in both study components. Potential policies to address consumer confusion include requiring disclosure of WG content as a percentage of total grain content or requiring disclosure of the grams of WG v . refined grains per serving.